Rational, emotional, and social drivers of hotel booking intention : a hybrid CB-SEM - FSQCA approach - Pérez-Ricardo, Elizabeth del Carmen; García-Mestanza, Josefa (ELSEVIER, 2026)
This study explores the key factors influencing tourists’ booking intentions in hotels by integrating rational, emotional, and social dimensions. Using a hybrid methodological approach, data from 390 customers were analyzed through Covariance-Based Structural Equation Modeling and Fuzzy-Set Qualitative Comparative Analysis (fsQCA). The results show that rational factors have the strongest impact on booking decisions. However, fsQCA reveals that multiple combinations of factors can also lead to high booking intention. From a managerial perspective, the findings suggest that hotel managers should not only focus on rational elements but also incorporate emotional and social aspects into their strategies to personalize offerings and better align with guest expectations. This study contributes to tourism and hospitality research by proposing a theoretically integrated framework that captures the interplay of rational, emotional, and social dimensions in shaping hotel booking intentions. Applying a hybrid CB-SEM-fsQCA design within the hotel industry context, it offers nuanced insights into consumer decision-making processes that strengthen both theoretical understanding and managerial implications.
Disponible online desde el 3 de diciembre de 2025
Keywords: Turismo - Investigación; Hoteles y pensiones; Hostelería; Booking intention; Rational factors; Emotional factors; Social factors; CB-SEM; FsQCA